Validation of Death and Dying Distress Scale-Chinese Version and Prevalence of Death Anxiety Among Patients With Advanced Cancer - Tang, Lili; Zhang, Yening; Pang, Ying; Zhou, Yuhe; Li, Jinjiang; Song, Lili; He, Yi; Li, Zimeng; Wang, Yan (Frontiers in Psychiatry, 2021)
Purpose: Death anxiety is commonly experienced by individuals with advanced cancer who have a limited life expectancy. The Death and Dying Distress Scale (DADDS) is a validated measure that was created to capture this experience; but no Chinese version is available to date. We conducted a cross-sectional study to explore the psychometric properties of a Chinese version (DADDS-C) and address prevalence of death anxiety among patients with advance cancer. Methods: Patients with advanced cancer were recruited from Peking University Cancer Hospital. Measures administered included: DADDS-C, Patient Health Questionnaire (PHQ-9), General Anxiety Disorder-7(GAD-7), Quality of Life at End of Life in Cancer (QUAL-EC), Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being Scale (FACIT-sp). McDonald’s Omega, Cronbach’s alpha, Exploratory Factor Analysis and Confirmatory Factor Analysis were used to test DADDS-C’s reliability and validity. Logistic regression analysis was used to identify risk factors for death anxiety. Results: Of 300 patients approached, 256 (85%) provided informed consent and completed the questionnaires. Of these participants, 43 (16.8%) had moderate death anxiety based on scores of ≥45 on the DADDS-C. Three factors (feeling shortness of time, dying and death distress, being a burden to others) explained 71.643% of shared variation with factor loadings ranging from 0.629 to 0.822. Cronbach’s alpha was 0.939; Omega total was 0.959. DADDS-C had acceptable convergent and discriminant validity. Logistic regression analysis indicated that two factors (better relationship with healthcare providers and preparation for end of life) protected patients from death anxiety. Conclusion: DADDS-C is a valid tool for measuring death anxiety in Chinese patients with advanced cancer. The presence of at least moderate death anxiety in a substantial minority of these patients calls for screening for this symptom and for more routine psychological interventions to alleviate and prevent such distress in this population.